Protagonismo juvenil: uma avaliação do programa agente jovem de desenvolvimento humano na cidade de Natal RN (2006/2007). - Almeida, Jussara Keilla Batista do Nascimento (2009)
This paper presents a critical rescue of the term youth, while simultaneously is presented as the lifetime of between 15 and 24 years. Rescue two features in the literature. The first considers youth as a transition period and the second phase work that from a predisposition to rebellion. Discusses the design plural of that term, youth recital to this social and historical aspects of different societies to which it relates and highlights the importance of realizing the diversity of it. Where the object of investigation, the Young Agent Program, the overall objective of the study is to evaluate the effectiveness of the actions of the Young Agent Program for Human Development in Natal-RN. Specifically aims to evaluate the effectiveness of the Young Agent Program: a) as an enhancer of the integration of young people in social spaces of family, school and community, b) as to (re) insertion and the incorporation of issues related to health in adolescence, and c ) regarding the work of young people as multipliers of the actions of the program. With regard to the methodological procedures presents a review of the literature on youth, and the categories of human development, leadership and evaluation of youth policies for the construction of theoretical and analytical approach, using documentary data collection in the Municipal Labor and Social Services - SEMT on the Young Agent Program, and interviews with actors involved in the program. Finally, evaluates the effectiveness of the Young Agent Program from the perspective of participants